Desarrollo de las relaciones objetales en una niña de 7 años - Soto Ramírez, Magali Leticia (2025)
The objective of this work is to provide knowledge, through a clinical case study, on how object relations have been developed in a 7-year-old girl, who is in the second grade of primary education. By means of a descriptive design, we will describe how and in what way object relations have been established in the minor, who presents difficulties in her academic performance and also difficulties of an emotional nature, a problem corroborated by the mother and the school psychologist. First, we contacted the school management and the head of the psychology area of the school, who requested an interview with the parents or guardians of the minor and then proceeded to interview the girl's mother for the subsequent preparation of the clinical history. Subsequently, the school psychologist introduces us to the child. After meeting her, we initially established a rapport with the child, conducted the interview and then the psychological evaluation, using the Child Thematic Aperture Test C.A.T.; Free Drawing; Drawing of the Kinetic Family (eating); Duss Fables Test (awakening) and ending with Bender's visuomotor gestalt test. We were able to observe in a relevant way problems at an emotional level that respond to the failures in the bonds established within her development with the parental figures, to the family dysfunction in which she is immersed and to the history of violence experienced by the child.